Serial serum brain-type natriuretic peptide (BNP) identifies compromised blood flow in infants with hemodynamically significant patent ductus arteriosus - Yasser Elsayed; Mary Seshia; Ronald J. Baier; Shyamala Dakshinamurti (Hygeia Press di Corridori Marinella, 2017)
Background: The physiological correlates of elevated serum brain-type natriuretic peptide (BNP) in hemodynamically significant patent ductus arteriosus (HSPDA) are unclear. Objective: To determine if serial BNP measured at 48-72 hours of age, before and after non-steroidal anti-inflammatory drugs (NSAID) treatment of HSPDA reflect compromised blood flow indices, in infants < 31 weeks of gestational age (GA). Design/methods: In a prospective blinded study, 70 infants < 31 weeks GA, admitted to Winnipeg NICUs from August 2010 to September 2011, had serum BNPs and echocardiograms at 48-72 hours of age, before and after medical treatment of HSPDA. All BNP and logarithm of BNP (logBNP) were correlated by linear regression with contemporaneous blood flow indices for: 1) systemic hemodynamic indices (corrected left and right ventricular outputs [LVO, RVO], RVO/LVO ratio, superior vena cava flow [SVCF], SVCF/LVO); 2) regional blood flow indices (middle cerebral artery flow [MCAF], MCAF/LVO ratio, middle cerebral artery resistive index [MCARI], middle cerebral artery pulsatility index [MCAPI]; celiac artery flow [CAF], CAF/LVO ratio, celiac artery resistive index [CARI], and celiac artery pulsatility index [CAPI]). Results: Twenty-six of 70 infants developed HSPDA at 6 ± 2 days. Both BNP and logBNP had similar correlations with all indices, but logBNP showed better goodness of fit. The best correlation was at 48-72 hours of life. Analyzing systemic hemodynamics, logBNP best correlated with SVCF (β -0.49, R2 0.24, p < 0.0001), SVCF/LVO (β -0.55, R2 0.31, p < 0.0001), RVO/LVO (β -0.59, R2 0.35, p < 0.0001), LVO (β 0.4, R2 0.16, p < 0.0001), and RVO (β -0.35, R2 0.12, p < 0.0001). For regional blood flow, logBNP best correlated with MCARI (β 0.6, R2 0.35, p < 0.0001), MCAPI (β 0.5, R2 0.29, p < 0.001), and MCAF (β -0.34, R2 0.12, p < 0.0001). Conclusions: BNP correlates with blood flow indices in preterm infants with HSPDA mainly at 48-72 hours reflecting the value of pre-symptomatic physiologic prediction by BNP.